SOME FIXED POINT RESULTS FOR CIRIC OPERATORS IN B-METRIC SPACES - Mohanta, S. K.; Maitra, R. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2016)
Fixed points for Ciric operators satisfying some generalized contractive type conditions are obtained in the setting of $b$-metric spaces. Moreover, we investigate that these operators satisfy property $P$. Finally, strength of hypothesis made in main theorem has been weighed through an illustrative example.